Correlation between echocardiographic measurements and right heart hemodynamic parameters in patients undergoing evaluation for pulmonary hypertension. Issue 5 (15th September 2022) - Hosseini, Omid; Daines, Benjamin; Rao, Sanjana; Yang, Shengping; Test, Victor; Sethi, Pooja; Prieto, Sofia; Abdelmalek, John; Elmassry, Mohamed; Nugent, Kenneth
Abstract: Echocardiograms provide important information for the evaluation and management of patients with pulmonary hypertension. Right ventricular free wall strain measurements provide additional information about the longitudinal contractile function of the right ventricle. Clinical information, including echocardiographic measurements and right heart hemodynamic parameters, on patients undergoing right heart catheterization for evaluation of possible pulmonary hypertension was collected retrospectively. This study included 60 patients (35 women) with a mean age of 62.6 ± 14.8 years. For World Health Organization categories, 32 patients were in Group 1, 12 in Group 2, 4 in Group 3, 3 in Group 4, and 7 had mixed clinical features of both Group 2 and Group 3. The mean pulmonary artery pressure was 40.6 ± 13.2 mm Hg. The right atrial volume index had significant positive correlations with the brain natriuretic peptide level, right ventricular volume index, left atrial volume index, and right atrial pressure and negative correlations with the cardiac index and mixed venous oxygen saturation. The mean right ventricular free wall strain was −17.85 ± 5.56%; it did not have significant correlations with right heart hemodynamic parameters. Therefore, the right atrial volume index but not the right ventricular strain index provides important objective information for the evaluation of patients with possible pulmonary hypertension.